A Rare Case of Ewing’s Sarcoma in Pregnancy - Kumar, Amit; Sindhusha, P.; Satyavathi, P. J. N.; Vanajakshi, A.; Annapoorna, S. (Journal of Pharmacy Practice and Community Medicine)
Ewing’s sarcoma (ES) is a rare cancerous tumor of bone or soft tissue that usually occurs mostly in young adults (teens through mid-20s). It is very rare to diagnose ES in pregnancy. Only a few cases have been reported in a pregnant patient of ES. The treatment will be based on the size of the bone tumor. Chemotherapy is much required for the first treatment for localized ES of the bone. It is used before surgery or radiation therapy. This is called neoadjuvant chemotherapy. Here we report a rare case of a 24-year female with an Ewing’s sarcoma, located in the pelvic bone detected in the 3rd trimester of pregnancy treated successfully in G.S.L medical college and hospital. Overall maternal and fetal outcomes are good when treatment is administered promptly and under the care of a multi- disciplinary team.
Keywords: Chemotherapy; Ewing’s sarcoma; Pregnancy; Pelvic mass; Intrauterine growth restriction.